Generic competencies and practices of managing by competencies: an exploratory study in different organizational contexts - André, Ana Rita; Rodrigues, Ana Cláudia (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Given the increasingly demanding labor market, today’s professional should act according to certain generic competencies, which allows him to perform as required by the contemporary world. In parallel, human resource management (HRM) current trends, highlight the importance that managing by competencies has in the organizational context, in the sense that it impels a more strategic and integrated HRM. The evidence of the theoretical and practical pertinence of this theme resulted in an exploratory study of a qualitative nature, which findings lead us to conclude that the most valued generic competencies by firms are flexibility, interpersonal relationship, adjustment to change and teamwork. Another finding is that HRM managing by competencies practices is characterized by informality. Managing by competencies is more frequent presence in processes as: recruitment, retention and in the employees’ development plans.